1994
DOI: 10.1063/1.358538
|View full text |Cite
|
Sign up to set email alerts
|

FMR studies of magnetic properties of Co and Fe thin films on Al2O3 and MgO substrates

Abstract: The effect of substrates on the magnetic properties has been studied for Co and Fe films both on Al2O3 (112̄0) and MgO (001) substrates by using ferromagnetic resonance techniques. For Fe(001)/MgO(001) samples the thickness dependence of the magnetocrystalline constant and of the effective magnetization values have been determined from the in-plane angular variation of the resonance field H0. Different reasons for the thickness dependencies of these parameters are discussed. For Co(111)/Al2O3(112̄0) the angula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The magnetic properties of Fe films deposited on MgO are known to be thickness dependent: a decrease in the crystalline anisotropy with decreasing thickness L has been indeed observed. [26][27][28][29] It has been attributed to a 1 / L contribution arising from surface anisotropy due to strains induced by the mismatch between film and substrate. 28,29 The recovering of the bulk properties for a 35-nm-thick film agrees with a previous study where the 1 / L term is found to be smaller for films prepared at 470 K than at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic properties of Fe films deposited on MgO are known to be thickness dependent: a decrease in the crystalline anisotropy with decreasing thickness L has been indeed observed. [26][27][28][29] It has been attributed to a 1 / L contribution arising from surface anisotropy due to strains induced by the mismatch between film and substrate. 28,29 The recovering of the bulk properties for a 35-nm-thick film agrees with a previous study where the 1 / L term is found to be smaller for films prepared at 470 K than at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] It has been attributed to a 1 / L contribution arising from surface anisotropy due to strains induced by the mismatch between film and substrate. 28,29 The recovering of the bulk properties for a 35-nm-thick film agrees with a previous study where the 1 / L term is found to be smaller for films prepared at 470 K than at room temperature. In the same manner, in our case, the annealing at 450°C can reduce the distance from the film surface where relaxation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their epitaxial character, the expected in-plane cubic anisotropy has experimentally been found in the Fe/MgO(001) system, with an in-plane anisotropy and the easy axis along the 100 in plane directions. Early works of Goryunov et al [96,97] determined the magnetic anisotropy for Fe films of different thicknesses sputtered on MgO(001) substrates. Assuming the weak electronic interaction at the Fe-MgO interface, their goal was to explore the relevance of the mismatch induced strain on the magnetic anisotropy of the system.…”
Section: Fe On Mgo(001): Magnetic Properties and Magnetization Revers...mentioning
confidence: 99%
“…MgO(0 0 1) is the substrate most frequently used due to its catalytic application and its stability at high temperature [6,7]; many works have been published on the growth of Co on MgO [1][2][3][8][9][10][11][12][13][14][15][16][17], with different experimental growth methods and many different analyzing techniques. Different studies demonstrate a 3D growth with fcc Co crystallographic structure at the early stage of growth [8,2].…”
Section: Introductionmentioning
confidence: 99%